Rotationally state-selected ion-molecule reactions studied using pulsed-field ionization techniques - Mackenzie, S; Halse, E; Merkt, F; Softley, T (1995)
A new method for studying state-selected bimolecular ion-molecule reactions is presented here, based on the technique of zero-kinetic-energy (ZEKE) photoelectron spectroscopy. State selection of the molecular ions is achieved by two-color laser excitation to high Rydberg states, followed by pulsed-field ionization of the Rydberg molecules. The ions are produced in unique vibration-rotation levels with 100% discrimination against other ions present. They are formed in a supersonic beam and accelerated so as to react with other neutral molecules present in the beam, with controlled collision energy variable in the range 10 meV to 1 eV. The product ions are detected using a quadrupole mass-filter, and the reaction probability is determined as a function of collision energy and of reactant ion quantum state by measuring the product ion/parent ion ratio. State selection of N 2+, NO +, CO + and H 2+ in a range of rotational levels has been achieved, all in the vibrational ground state, and preliminary measurements of the reaction H 2+ plus H 2 yields H 3+ plus H have been made. The study of other reactions is currently in progress. Some new observations have also been made in the same apparatus concerning the decay dynamics of high Rydberg states of N 2 which are of relevance to the state-selection process. The dynamics are followed as a function of principal quantum number and the effects of a weak electric field in promoting stabilization are observed.